Assessment of critical water-related data and skills needs to improve anticipatory actions in selected districts of the Somali Region, Ethiopia - Assefa, T. T.; Ebrahim, Girma Yimer; Taye, Meron Teferi; Ruckstuhl, Sandra (International Water Management Institute, 2024)
The brief identifies critical gaps in water-related data and skills necessary for the effective implementation of anticipatory water management actions in response to climate change in the Dolo Ado and Bokolmayo districts, Ethiopia. It evaluates current community and local government practices and recommends improvements in data collection, capacity building, and integrated water management to enhance resilience against droughts and floods. Key findings highlight the need for better data monitoring, early warning systems, and infrastructure investment to mitigate water-related hazards and improve local adaptive capacities.